Analisis Kemampuan Berpikir Kritis Matematika pada Keterampilan Abad 21 Berdasarkan Konsep Diri - Riduan Febriandi; Tatang Herman; Turmudi Turmudi (Journal of Elementary School (JOES), 2022)
This study aims to determine the critical thinking skills of SD Negeri Babakan Priangan 123 elementary school students in Bandung, which is viewed from the aspect of self-concept in solving problems on the material around square and rectangle. Indicators of critical thinking skills used in this study are interpretation, analysis, evaluation, inference, explanation and self-regulation which are reviewed on self-concept with dimensions of indicators, expectations and assessments. The method used in this research is qualitative. The subjects in this study were fourth grade students at SDN Babakan Priangan 123 Bandung City, which opened 28 students. The research instrument used test questions, observation sheets and interview guidelines. The validity of data processing used triangulation techniques, namely reducing data, presenting data and drawing conclusions. From the research results obtained through data analysis, it is known that critical thinking skills in terms of self-concept are still relatively low. The results of the study can provide information to teachers or lecturers regarding mathematical critical thinking skills in terms of self-concept aspects, so that teachers are expected to design a learning model or learning media that improves students' critical thinking skills and self-concept. Keywords: Analysis, Critical Thinking, Mathematics, Self Concept